A domestic rooftop PV system: a step towards retrofitting the built environment to combat climate change in Bahrain - Alnaser, Naser W. (Frontiers in Built Environment, 2023)
This article assesses the technological, economic, and environmental aspects of installing the first 7.8 kW PV installation on a rooftop of a domestic house in Bahrain for a period of 2 years (20th March 2018 to 31st March 2020). The maximum solar electricity generated was 1,228.9 kWh (August 2018), and the least was 728.16 kWh (December 2019). The maximum daily specific yield (SY) was 6.12 kWh/kWp (on 14 April 2019). The annual average daily specific yield for this domestic building was 4.13 kWh/kWp. The average performance ratio (PR) of the PV system was 73.0% in 2019. The self-sufficiency (SS) of this installation was found to vary from 15.3% to 50.7%. The average SS value in 2018 was 22.8%, while in 2019 it was 28.6%. Furthermore, a cubic relation correlation was established, relating the month number (X) and the monthly average of the daily specific yield (Y). It was found that installing a solar PV system will cut about 39.0% of CO2 annually, which is equal to 4.637 tons and hence saves 38,567 ft3 of natural gas. The initiative of encouraging the use of rooftops in Bahrain to produce zero-carbon electricity is a step towards retrofitting the built environment to combat climate change.